Microculture for the isolation of Leishmania, modified to increase efficacy: a follow-up to a previous study - Ihalamulla, R.L.; Rajapaksa, U.S.; Karunaweera, N.D. (My University, 2006)
In studies on the leishmaniases, the identification of the parasites to species level, by iso-enzyme characterization or by most molecular biological techniques, requires the isolation of the parasites in culture. Novy, McNeal and Nicolle (NNN) and Evan’s modified Tobie’s (EMTb) are two conventional media commonly used for the isolation of Leishmania parasites from blood or tissue samples of patients. Both are biphasic, with a solid agar layer that has to be enriched with blood, and EMTb medium is based on relatively expensive reagents. The preparation of both of these media is laborious and time-consuming, and neither supports the multiplication of all Leishmania parasites from humans (Allahverdiyev et al., 2004; Ihalamulla et al., 2005). A monophasicmicroculture (MCC) method that only uses very small volumes of RPMI 1640 supplemented with 20%foetal calf serum (FCS) has recently been described by Ihalamulla et al. (2005). In the detection of human cutaneous leishmaniasis in Sri Lanka, this method,.....